2006
DOI: 10.1242/dev.02650
|View full text |Cite
|
Sign up to set email alerts
|

Bchs, a BEACH domain protein, antagonizes Rab11 in synapse morphogenesis and other developmental events

Abstract: BEACH proteins, an evolutionarily conserved family characterized by the presence of a BEACH (Beige and Chédiak-Higashi) domain, have been implicated in membrane trafficking, but how they interact with the membrane trafficking machinery is unknown. Here we show that the Drosophila BEACH protein Bchs (Blue cheese) acts during development as an antagonist of Rab11, a small GTPase involved in vesicle trafficking. We find that reduction in, or loss of, bchs function restores viability and normal bristle development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 50 publications
8
113
0
Order By: Relevance
“…bchs has extensive homology to ALFY throughout the entire sequence and consistent with the mouse tissue expression profile of ALFY (highest in the brain), 47 bchs seems to be selectively expressed in the fly brain. 85 Moreover, adult flies lacking bchs accumulate ubiquitin-positive inclusions and display a neurodegenerative phenotype, 73 in line with the proposed function of ALFY in autophagic degradation of aggregate-prone proteins. In a screen for genetic modifiers of a gain-of-function (GOF) rough eye phenotype caused by overexpression of bchs, the small GTPase Rab11 was found to enhance this phenotype.…”
Section: Alfy Homologsmentioning
confidence: 54%
See 1 more Smart Citation
“…bchs has extensive homology to ALFY throughout the entire sequence and consistent with the mouse tissue expression profile of ALFY (highest in the brain), 47 bchs seems to be selectively expressed in the fly brain. 85 Moreover, adult flies lacking bchs accumulate ubiquitin-positive inclusions and display a neurodegenerative phenotype, 73 in line with the proposed function of ALFY in autophagic degradation of aggregate-prone proteins. In a screen for genetic modifiers of a gain-of-function (GOF) rough eye phenotype caused by overexpression of bchs, the small GTPase Rab11 was found to enhance this phenotype.…”
Section: Alfy Homologsmentioning
confidence: 54%
“…In a screen for genetic modifiers of a gain-of-function (GOF) rough eye phenotype caused by overexpression of bchs, the small GTPase Rab11 was found to enhance this phenotype. Moreover, loss of bchs was found to strongly suppress developmental defects exhibited by rab11 loss-of-function mutants, 85 suggesting that bchs functions during Drosophila development as an antagonist of Rab11-mediated vesicle trafficking. Interestingly, the presence of a putative TBC domain in ALFY/bchs might indicate that bchs negatively regulates Rab11 by promoting its GTPase activity.…”
Section: Alfy Homologsmentioning
confidence: 99%
“…These include Rab11, a GTPase that regulates recycling endosomes; the early endosomal protein Spichthyin (Spict); Dap160/intersectin; Spinster, a component of late endosomes; endophilin, synaptojanin, and AP180, regulators of clathrin-mediated endocytosis; Dynamin, which is required for membrane fission; and the F-BAR protein Nervous wreck (Nwk) (Sweeney and Davis 2002;Coyle et al 2004;Koh et al 2004;Marie et al 2004;Dickman et al 2006;Khodosh et al 2006;Wang et al 2007). In particular, Dickman et al (2006) observed that many endocytosis mutants exhibit overgrowth in the form of satellite boutons ( Figure 5C).…”
Section: Mechanisms Regulating Growth and Plasticitymentioning
confidence: 99%
“…The mammalian homolog of Drosophila Lethal giant larvae (Lgl1) is shown to control axonal outgrowth by activating Rab10 (Wang et al, 2011a). In addition, Drosophila Rab11 is required for normal synaptic morphogenesis at the neuromuscular junction (NMJ) (Khodosh et al, 2006). Finally, mammalian Rab17 is shown to play an essential role in the regulation of dendritic morphogenesis and postsynaptic development (Mori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%